Reconstructing Legal Accountability Mechanisms for Climate-Induced Migration Through Integrative Social-Environmental Justice Frameworks - Dahlia Kusuma Dewi; Dio Prasetyo Budi; hafiza binti abdul samath (International Forum of Researchers and Lecturers, 2024)
Climate-induced migration is becoming an increasingly significant global issue, driven by environmental changes such as rising sea levels, extreme weather events, and resource scarcity. Despite its growing importance, current legal frameworks inadequately address the protection of climate migrants, leaving them vulnerable and without clear legal rights. This research aims to propose an integrated social-environmental justice framework to address the legal accountability for climate-induced migration, focusing on the recognition of migrant rights, state responsibilities, and environmental protection. The study uses a comparative legal analysis to examine legal systems across various countries and incorporates field data from climate-vulnerable coastal communities through interviews, surveys, and legal case reviews. The research finds that the proposed framework enhances migrant recognition and clarifies state responsibilities in 70% of reviewed legal cases, offering a more comprehensive solution compared to traditional environmental and human rights approaches. The framework's integration of legal, social, and environmental elements provides a holistic response to climate migration, emphasizing equity and sustainability. However, challenges such as political resistance, fragmented governance, and limited funding hinder full implementation. The study concludes by recommending that governments and international bodies adopt this framework and strengthen their commitment to legal protections and climate adaptation strategies for displaced populations. Further research should focus on refining legal frameworks, addressing implementation barriers, and expanding the scope of social-environmental justice to better support climate migrants.